2002
DOI: 10.1128/iai.70.3.1538-1546.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Expression Patterns Differ within Anatomically Distinct Regions of the Genital Tract duringChlamydia trachomatisInfection

Abstract: Untreated infections with Chlamydia trachomatis commonly result in ascending infection to fallopian tubes and subsequent immune-mediated tubal pathology in females. The proposed immune-mediated injury may be associated with the increased recruitment of CD4 cells to the upper genital tract (GT) (oviducts) in comparison to the lower GT (cervix) during infection, as shown in animal models. To understand the mechanisms responsible for this biased recruitment of CD4 cells within the GT, we characterized chemokine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
53
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 35 publications
13
53
0
1
Order By: Relevance
“…Further, investigations have shown that CD4 ϩ Th1 and not Th2 cells are required for Chlamydia resolution in a gamma interferon (IFN-␥)-dependent manner (17,20). Consistent with a predominant role of Th1 cells, Th1-cell-associated chemokines CCL5/RANTES and CXCL10/IFN-␥-inducible protein 10 (IP-10) were shown to be primarily induced in infected genital tissue (6,34). Further, unpublished data from our laboratory demonstrates that the corresponding receptor for CXCL10, CXCR3, plays a role in the recruitment of Th1 cells during chlamydial infection.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Further, investigations have shown that CD4 ϩ Th1 and not Th2 cells are required for Chlamydia resolution in a gamma interferon (IFN-␥)-dependent manner (17,20). Consistent with a predominant role of Th1 cells, Th1-cell-associated chemokines CCL5/RANTES and CXCL10/IFN-␥-inducible protein 10 (IP-10) were shown to be primarily induced in infected genital tissue (6,34). Further, unpublished data from our laboratory demonstrates that the corresponding receptor for CXCL10, CXCR3, plays a role in the recruitment of Th1 cells during chlamydial infection.…”
supporting
confidence: 63%
“…We previously reported that chemokines associated with Th1 cell recruitment are induced in the genital tract within 3 to 7 days after Chlamydia infection and are preferentially expressed in OD tissue compared to CV tissue (34), and we have recently demonstrated a functional role of these chemokines in the chemotaxis of Chlamydia-specific lymphocytes (unpublished data). To determine whether the inoculative dose of Chlamydia affected the distribution or magnitude of induction of Th1-associated chemokines, we measured the CXCR3 ligand CXCL10/IP-10 by ELISA in clarified OD and CV tissue homogenates (Fig.…”
Section: Fig 3 Course Of Infection By Vaginal Swabs and Tissue Homomentioning
confidence: 77%
“…However, the existing data set was notable for the absence of some expected key inflammatory mediators, such as tumor necrosis factor alpha (TNF-␣) (3), IP-10 gamma interferon (IFN-␥)-inducible 10-kDa protein (CXCL10), and RANTES (CCL5) (44). This suggested that existing in vitro models based on epithelial tumor cell lines might not fully mimic the immunobiology of Chlamydia-infected epithelium.…”
mentioning
confidence: 99%
“…Murine studies using Chlamydia muridarum have greatly expanded the knowledge of infection kinetics, including the differential cell infiltration between the lower and upper genital tract, the rate at which this occurs, [18][19][20][21][22][23][24] and also the rate of infection ascension. [24][25][26] The infectious dose of Chlamydia is known to modulate the innate immune response, with greater inoculating doses causing a greater innate immune response.…”
Section: Infectionmentioning
confidence: 99%